UNRAVELING THE INFLUENCE OF BUILDING MATERIALS CRITERIA (BMC) ON HOTEL’S OPERATIONAL SUSTAINABILITY - Ismail, Nur Adlina; Khalil, Natasha; Abdullah Sani, Suwaibatul Islamiah (Journal of Surveying, Construction and Property, 2024)
The core business of hotels lies in the hotel buildings design and its service operation. As the hotels are concentrating more on aesthetics values as one aspect of perceived experiential value, a careful selection of materials is urgently needed for hotel sectors. It is important to identify the crucial criteria in choosing building materials towards the hotel’s operational sustainability. Thus, this paper aims to analyze the significance level building materials criteria (BMC) towards hotel’s operational sustainability. A quantitative approach was adopted via questionnaire surveys to 116 operation and maintenance manager that worked in 29 green rated hotels throughout Malaysia. The data is analysed using SmartPLS 4, a software with graphical user interface for variance-based structural equation modeling (SEM) using the partial least squares (PLS) path modeling method. Results from the SEM-PLS has supported three (3) hypothesis, that confirmed the manufacturers criteria, health criteria and resource management criteria, as the BMC variables has significance relationship towards hotel’s operational sustainability. This study significantly helps the developers, hoteliers, stakeholders, consultants, and designers to be aware of the applicability and suitability to be used in their projects. The findings provide practical insights for hotel operators and managers, offering guidance on selecting building materials aligned with sustainability goals. This operational focus can aid hotels in making informed decisions that enhance their overall sustainability performance.